Low Molecular Weight Heparin (Enoxaparin) Versus Oral Anticoagulant Therapy (Acenocoumarol) in the Long-Term Treatment of Deep Venous Thrombosis in the Elderly: a Randomized Trial - Veiga, F.; Escribá, A.; Maluenda, M. P.; Rubio, M. López; Margalet, I.; Lezana, A.; Gallego, J.; Ribera, J. M. (Thrombosis and Haemostasis, 2000)
This study aims to establish the relative effectiveness and safety of low molecular weight heparin in elderly patients with venous thrombosis in order to find an alternative to oral anticoagulant therapy with less bleeding complications in the long-term treatment of deep venous thrombosis (DVT).One hundred consecutive elderly patients (>75 years old) with venographically demonstrated proximal DVT were included in a randomized trial. All patients were treated for ten days with adjusted doses of intravenous heparin. Informed consent was obtained and on the eight day, patients were randomly allocated to receive acenocoumarol (INR 2.0-3.0) or subcutaneous enoxaparin (4000 anti-Xa units once a day) for three months. All patients were followed-up clinically and venographically for a one year period. The results were analyzed with Fisher’s exact test or chi-square test as appropriate.During the treatment and surveillance period, 6 of the 50 patients (12%) who received acenocoumarol and 8 of the 50 patients (16%) who received enoxaparin had new episodes of venous thromboembolism confirmed by objective testing (p = 0.6; 95% CI for the difference: −19.5 to 11.5). Hemorrhagic complications occurred in six of the 50 patients (12%) who received acenocoumarol and in one (2%) of those on enoxaparin (p = 0.1; 95% CI for the difference: -1.8 to 21.8). Vertebral fractures developed in 2 patients (4%) in the enoxaparin group (p = 0.5; 95% CI for the diference: −11.4 to 3.4).These results show that fixed dose enoxaparin seems to be effective and safe in the long-term treatment of proximal DVT in the elderly. In comparison with oral anticoagulants, the findings are inconclusive due to the wide confidence intervals for differences between outcomes, however they suggest that the former may have less bleeding complications with similar efficacy.
Keywords: Low molecular weight heparin; deep vein thrombosis; long-term treatment; secondary prophylaxis; elderly; randomized trial